2013
DOI: 10.1007/s13238-013-2114-1
|View full text |Cite
|
Sign up to set email alerts
|

Pannexin-1 influences peritoneal cavity cell population but is not involved in NLRP3 inflammasome activation

Abstract: Pannexin-1 (Panx1) forms nonselective large channel in cell plasma membrane and has been shown to be associated with NLRP3 inflammasome activation, ATP release and phagocytes recruitment. In the current study, by manipulation of Panx1 expression in human myeloid cells and application of Panx1 deficient mice, we failed to find a correlation between Panx1 and NLRP3 inflammasome activation, although an interaction between these two proteins was evident. However, in thioglycollate induced peritonitis, Panx1 defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 15 publications
(22 reference statements)
2
25
0
1
Order By: Relevance
“…Incubation of macrophages in a mimetic blocking peptide of Panx1, 10 Panx1 corresponding to the first extracellular loop of Panx1, but not a scrambled control, abolished ATP release in response to Eh and r Eh CP5, and prevented activation of caspase-1 and IL-1β [ 27 ] ( Fig 5A and 5C ). Similarly, we found that panx1 -/- macrophages, which had a normal inflammasome response to extracellular application of ATP and is consistent with other reports [ 28 , 29 ], did not activate the inflammasome in response to Eh ( Fig 5D ). Together, these data indicate that Panx1 channels conduct ATP into the extracellular space triggered by activation of α 5 β 1 integrin by Eh CP5.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Incubation of macrophages in a mimetic blocking peptide of Panx1, 10 Panx1 corresponding to the first extracellular loop of Panx1, but not a scrambled control, abolished ATP release in response to Eh and r Eh CP5, and prevented activation of caspase-1 and IL-1β [ 27 ] ( Fig 5A and 5C ). Similarly, we found that panx1 -/- macrophages, which had a normal inflammasome response to extracellular application of ATP and is consistent with other reports [ 28 , 29 ], did not activate the inflammasome in response to Eh ( Fig 5D ). Together, these data indicate that Panx1 channels conduct ATP into the extracellular space triggered by activation of α 5 β 1 integrin by Eh CP5.…”
Section: Resultssupporting
confidence: 93%
“…Finally to understand how α 5 β 1 integrin could regulate opening of Panx1 we tested two possibilities. First, whether this was by caspase cleavage of the Panx1 intracellular C-terminus, which has been shown to regulate ATP release in apoptotic immune cells [ 29 ]. However, we ruled this pathway out as we never observed a band shift or disappearance of any Panx1 glycoforms after Eh stimulation and ATP release was not sensitive to pan-caspase inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate whether Panx1 affects macrophage recruitment, we first performed chemotaxis experiments using BMDMs from Panx1 del Apoe −/− and Panx1 fl/fl Apoe −/− control mice. In agreement with earlier studies on Panx1 −/− macrophages 23 , 24 , deletion of Panx1 from BMDMs (Fig. 1F ) did not alter the chemotactic response to monocyte chemoattractant protein (MCP)-1 in these cells (Fig.…”
Section: Resultssupporting
confidence: 92%
“…They further noted that there was no defect in migration of macrophages lacking Panx1. In a similar study, Wang and team used pannexin knock-out mice to assess activation of the inflammasome and migration of inflammatory cells [78]. These studies also demonstrated that the macrophages derived from a Panx1 knock-out mouse had normal activation of the inflammasome.…”
Section: Pannexins and Immunitymentioning
confidence: 95%
“…In addition, neutrophil migration into inflammatory sites was normal. An unexpected finding was that the migration of macrophages in response to thioglycollate broth was actually enhanced rather than inhibited [78]. It must be pointed out that, to date, there are no reports indicating an immunodeficient phenotype for pannexin knock-out mice.…”
Section: Pannexins and Immunitymentioning
confidence: 98%